Cacao agroforestry systems do not increase pest and disease incidence compared with monocultures under good cultural management practices. (April 2020) - Armengot, Laura; Ferrari, Leone; Milz, Joachim; Velásquez, Fortunato; Hohmann, Pierre; Schneider, Monika
Abstract: Pests and diseases threaten cacao production worldwide. Agroforestry systems are traditionally seen by farmers as one of the causes of increased pest and disease incidence, in contrast with full-sun monocultures. Cultural management practices—e.g. regular tree pruning, frequent pod harvest, regular removal of infested pods, weed management—have been reported to be crucial for pest and disease management. We performed two experiments for the purpose of assessing the effect of (i) different cacao production systems, and (ii) the frequency of harvest and removal of infested pods on the incidence of pests and diseases and on the cacao yield. The first experiment was performed in a long-term system comparison trial in Bolivia, where data on pest and disease incidence were recorded for three years in five production systems: two monocultures and two agroforestry system under organic and conventional farming, and one successional agroforestry system, i.e. a high tree density multi-strata system. Pest and disease management did not differ between systems and relied on cultural management practices. Overall, the incidence of pests and diseases did not differ between production systems, which indicated they were not the driver of yield differences between them. Across production systems, only 14% of the pods were affected by pests and diseases; 70% of these were affected by frosty pod rot. More than 80% of the pods infected by frosty pod rot were removed before the sporulation phase. In the second experiment, the effects of the frequency of harvest and removal of infected pods—every 15 days versus every 25 days—on pest and disease incidence and yield were tested in four farmers' fields. Fortnightly harvest and diseased pod removal significantly decreased disease incidence and increased cacao yield, by 25% and 46% respectively. Our results show that cacao agroforestry systems do not increase pest and disease incidence compared with monocultures when good cultural management practices are implemented, which, in turn, can increase the productivity of the cacao plantations. Highlights: Cacao agroforests did not increase disease incidence compared with monocultures. Cultural management practices ensured low pest and disease incidence in all systems. Pests and diseases were not the drivers of differences in cacao yield between systems. Frosty pod rot was the main fungal disease, pests played a minor role.